Analisis Wacana Kritis Norman Fairclough Pernyataan Megawati: “Pak Jokowi Kalau nggak Ada PDI Perjuangan duh Kasihan dah” - Sandi, Putri Paradilah; ., Mayasari; Yusup, Eka (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Partai Demokrasi Indonesia Perjuangan (PDIP) held its 50th Anniversary celebration on January 10, 2023. During the celebration, Megawati as the Chairperson of the party mentioned, "Mr. Jokowi, if there is no PDI Perjuangan, I'm sorry,". The statement received applause from the audience at JIEXPO Kemayoran. The video of Megawati's statement was uploaded again by KompasTV through the Youtube channel and received various responses. This research uses a qualitative research method with a critical discourse analysis approach of the Norman Fairclough model. The purpose of this research is to dissect discourse in three dimensions, namely textual, discourse practices, and sociocultural practices. Textually, the use of linguistic elements in the form of diction and majas is found. The dimension of discourse practice can be seen from the parties involved in making the video from KompasTV media through the Youtube channel. The level of consumption of this discourse is not only consumed by subscribers, but the wider netizen can access the information and provide comments. The sociocultural dimension is divided into three, namely situational, institutional, and social. Situational saw the situation when Megawati's 50th anniversary of PDIP received a response of applause when delivering the discourse. Institutional shows that PDIP's vote share has decreased in the 2024 elections. Then the social level in the discourse consists of cultural and political elements.